2019
DOI: 10.1002/icd.2155
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing advanced Theory of Mind skills in primary school: A training study with 7‐ to 8‐year‐olds

Abstract: Recent evidence showed that it is possible to help children's Theory of Mind (ToM) development during preschool and middle childhood. This study aimed to promote advanced mentalizing skills in children attending Year 2 of primary school through a ToM training programme based on narratives followed by multiple‐choice questions and conversations about mental states. Participants were 49 children, aged between 7 and 8 years (Mage = 7.6 years; SD = 3.98 months), assigned to the experimental (27 children, 11 boys) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The mean age of the investigated populations in this age range was 5.98 years (range 43–60 months). N = 10 studies reported training effects in kindergarten age (range:43–60 months); n = 3 studies included older children attending elementary school (range 7–9 years) 34 , 35 , 39 . Socio-cognitive training in both groups was labelled as either ToM-training, storytelling, or metacognitive intervention with the overall aim for children to further develop socio-cognitive skills using tasks where they had to reflect on other person’s mental states and beliefs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of the investigated populations in this age range was 5.98 years (range 43–60 months). N = 10 studies reported training effects in kindergarten age (range:43–60 months); n = 3 studies included older children attending elementary school (range 7–9 years) 34 , 35 , 39 . Socio-cognitive training in both groups was labelled as either ToM-training, storytelling, or metacognitive intervention with the overall aim for children to further develop socio-cognitive skills using tasks where they had to reflect on other person’s mental states and beliefs.…”
Section: Resultsmentioning
confidence: 99%
“…Two to four training sessions per week were conducted 29 33 over five 27 to 20 weeks 28 . Training for children attending elementary school lasted 40–50 min to resemble the duration of a standard school lesson, and training was conducted up to five times per week 34 , 35 , 39 . Kindergarten age children participated in the training either individually 33 or in small groups of up to five children 27 32 , children in elementary school attended the training in small groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each topic (i.e., fairness, altruism, and delay of gratification ability), two stories have been invented or created based on children's ( Varela, 2014 ) or on scientific literature ( Larsen et al, 2017 ), with the aim of stimulating group reflection and understanding of one's own and other points of view. According to literature about the training programs ( Bianco et al, 2019 ; Bianco et al, 2021 ), each story was followed by four multiple-choice questions create with the purpose of verifying child's actual understanding of the content, his/her ability to put themselves in the shoes of the story characters (perspective-taking) and to stimulate the subsequent discussion.…”
Section: Methodsmentioning
confidence: 99%
“…The heart of ToM competence is achieved around four years of age when the child becomes capable of reasoning on how a person may be guided in their actions by wrong thoughts on reality (Wellman, 2018). Then, the competence becomes more and more mature across middle childhood (Bianco, Lombardi, et al, 2019;Bianco et al, 2021;Lecce, Bianco, Devine, & Hughes, 2017), preadolescence (Devine & Hughes, 2013) and adolescence . Interestingly, a meta-analysis of ToM studies in ageing showed that older adults score significantly poorer than their younger counterparts across a wide range of measures varying on the modality of assessment, with a mean effect size of the age-effect moderate in magnitude (Henry, Phillips, Ruffman, & Bailey, 2012).…”
Section: Theory Of Mind: Its Nature and Developmental Trendmentioning
confidence: 99%